PERANCANGAN SISTEM PENDAFTARAN PASIEN RAWAT JALAN RUMAH SAKIT MELALUI SHORT MESSAGE SERVICE GATEWAY (Studi Kasus: RS. Panti Wilasa Dr. Cipto Semarang) - Putra, Toni Wijanarko Adi (Jurnal Transformatika, 2018)
SMS Gateway technology used in the outpatient registration process is an applied technology in the field of information. Outpatient outpatient visits are an indication of the hospital's success in managing the public confidence of doctors and re-control of the hospital. Use of SMS Gateway System aims to facilitate the delivery of information through SMS cheap, short and readable for each recipient. This study aims to provide an outpatient registration system at Rumah Panti Wilasa Hospital "Dr. Cipto "and doctor's schedule information via SMS Gateway. The design of this SMS gateway system using System Development Life Cycle (SDLC) method with 5 stages is System Planning, System Analysis, System Implementation and System Maintenance). This application design provides an SMS Gateway based registration information system that generates queue numbers for doctor checks, doctor's schedules and delivery of re-control information for patients.
Keywords: SMS gateway; Registration; Doctor Re-Control; Patient Queue; Hospital